Space colonisation for procedural road generation - Fernandes, Gabriel (2018)
Procedural road layout generation has been traditionally approached using L-Systems, with some works exploring alternative avenues. Although originally conceived for biological systems modelling, the adequacy of L-Systems as a base for road generation has been demonstrated in several works. In this context, we present an alternative approach for procedural road layout generation that is also inspired by plant generation algorithms: space colonisation. In particular, we use the concept of attraction points introduced in space colonisation as the base of our approach to produce road layouts, both in urban and inter-city environments. As will be shown, the usage of attraction points provides an intuitive way to parameterise a road layout. Our method can also be used with flow-fields, demographics, geographical, and boundary maps to further fine tune the layout.